Vitrificação de oócitos imaturos de eqüinos : características morfológicas ultra-estruturais e maturação nuclear in vitro - Curcio, Bruna da Rosa (2006)
The aim of the study was to investigate: 1) the ultrastructural morphologic characteristics in equine oocytes subjected to different times of exposure to cryoprotectant solutions and 2) the effect of initial cumulus morphology and cryoprotectants in the nuclear in vitro maturation (IVM) of the vitrified immature equine oocytes. The oocytes were obtained from ovaries from a slaughterhouse. In the first study 30 oocytes where divided in three groups: Control group (G1, n=10); Group 2 (G2, n=10), the oocytes were vitrified for exposure to VS-1 for 3min and VS-2 for 1min; Group 3 (G3, n=10), exposure to VS1 for 1.5min and VS-2 for 30sec. The oocytes were vitrified in open-pulledstraws (OPS). The ultrastructural characteristics where observed using a transmission electron microscope. The oocytes were classified as: I) oocytes morphologically normal; II) oocytes which presented intermediate damage but had completed organelles, and III) oocytes with severe morphological abnormalities. In the second study, compact (Ccp; n=248) and expanded (Cex; n=264) cumulus oocyte complexes were divided in three groups: Control, Treatment-1 (T1 - Ethylene glycol-EG + Dimetyl sulfoxide-DMSO + SIB) and Treatment-2 (T2 - Formamide + EG + DMSO + Polyvinylpyrrolidone + SIB). The control group was immediately matured in vitro, the other immature oocytes were vitrified in OPS and then matured in vitro. The maturation stage was observed under a fluorescence microscope (Hoechst 33342). The results of ultrastructural morphology were rated as Class I: 80% oocytes of G1, 30% of G2 and 60% of G3; Class II: 0% oocytes of G1, 20% of G2 and 30% of G3 30%, and Class III: 20% oocytes of G1, 50% of G2 and 10% of G3. The maturation rates (metaphase II - MII) were: 41% Control group, 38,3% T1 and 33,3% T2 (P>0,05). In the control group, the MII rates were higher in Cex oocytes (53,2%) than those Cco oocytes (29,3%; P<0,05). The initial cumulus morphology didn t significantly affect MII rates after vitrification (P>0,05). However, Cex oocytes had higher MII rates than Ccp oocytes in T1 (50% vs 27,3%) and T2 (45,7% vs 21,6%). It can be concluded that the reduction in time of exposure to cryoprotectant solutions resulted in better preservation of ultrastructural characteristics of equine oocytes submitted to vitrification. Immature equine oocytes can be IVM after vitrification/re-warming, and satisfactory MII rates can be obtained. The initial cumulus morphology did not affect nuclear in vitro maturation of equine oocytes after vitrification.